Purificação e caracterização de um novo inibidor de tripsina das sementes de Bauhinia pulchella BENTH. e seu potencial anticoagulante - ROMA, Renato Rodrigues (2021)
Proteases inhibitors (IPs) are molecules that regulate and control the activity of proteases. These inhibitors are classified according to their target proteases. Trypsin inhibitors belong to the class of serine protease inhibitors, and have the ability to regulate the action of trypsin and other serine enzymes. They can act in many physiological processes such as inflammation, metastasis and blood clotting. These inhibitors are commonly described in plants of the Fabaceae family, and can constitute up to 10% of the total soluble proteins. Species of the genus Bauhinia are sources of biologically active compounds and contain high concentrations of protease inhibitors. Therefore, the aim of this study was to purify and characterize a new Bauhinia pulchella seed inhibitor with anticoagulant activity. The inhibitor was purified by affinity chromatography in the trypsin-Sepharose 4B column, with protein yield of 43.1%, receiving the name BpTI (Bauhinia pulchella trypsin inhibitor) with apparent molecular mass of 20 kDa, specificity to bovine trypsin and with glycosylation (1.15%) in its structure. BpTI is an uncompetitive inhibitor that has IC50 (3 x 10-6 M) and Ki (1.05 x 10-6 M). And great stability to temperature and pH variations, as it maintained its inhibiting activity for 30 minutes at 100 ºC and in extreme pH ranges. However, the inhibitor is susceptible to reducing agents, such as DTT, which was able to completely inhibit its inhibitory activity. The entire BpTI was able to induce in vitro an anticoagulant effect at the concentration of 33 uM, prolonging the coagulation time in the intrinsic and common pathways, results that encourage further in vivo studies, prospecting it as a natural antithrombotic agent.